2021
DOI: 10.1016/j.scs.2021.103144
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of the built environment on the incidence rate of COVID-19: A case study of King County, Washington

Abstract: With COVID-19 prevalent worldwide, current studies have focused on the factors influencing the epidemic. In particular, the built environment deserves immediate attention to produce place-specific strategies to prevent the further spread of coronavirus. This research assessed the impact of the built environment on the incidence rate in King County, US and explored methods of researching infectious diseases in urban areas. Using principal component analysis and the Pearson correlation coefficient to process the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…In addition to, infection risk, migration of people comes out to be another reason for change in mobility pattern (Beria et al, 2021 ). In a built environment, if we increase the open space the incident rate decreases and overcrowding results in increase in infection probability (Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to, infection risk, migration of people comes out to be another reason for change in mobility pattern (Beria et al, 2021 ). In a built environment, if we increase the open space the incident rate decreases and overcrowding results in increase in infection probability (Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study is significant because it provides strong scientific evidence that demonstrates the associations between the built environment and COVID-19 transmission based on large-scale individualized data. While previous studies have suggested the associations based on summarized data (e.g., density of household types, COVID-19 transmission rate at the ZIP code scale 15 ), the current study provided a more stringent investigation by controlling various confounders, such as age and sex.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, the mitigation of viral transmission through the air delivery system can reduce the transmission of the virus. Nevertheless, current studies on the relationships between the built environment and COVID-19 transmission are still plagued by small sample sizes 13 , lack of precision, and relying on reports at county 16 , city 7 , ZIP code 15 , and community levels 12 . Stringent studies at the individual level are still lacking, most likely due to the high cost of acquiring data and the difficulty of controlling confounding covariates in prior methods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tosepu et al (2020) applied Spearman rank correlation analysis to associate weather conditions with COVID-19 Wu et al (2020 .a) applied binomial regression and found that 1 µ g/m 3 increased in PM 2.5 concentration was associated with the COVID-19 death rate by 8 %, after evaluating death counts for more than 3000 counties in the United States (representing 98% of the population of entire USA) up to April 22, 2020 Gupta (2020) . used descriptive analysis to study the effects of weather conditions (e.g., temperature, wind, humidity) on the virus spread Liu et al (2021) . used principal component analysis and the Pearson correlation coefficient to build a multiple linear regression model to investigate the impact of the built environment and urban density on the incident rate of COVID-19.…”
Section: Resultsmentioning
confidence: 99%